Evaluation of the Oncogenic Human Papillomavirus DNA Test with Liquid-Based Cytology in Primary Cervical Cancer Screening and the Importance of the ASC/SIL Ratio: A Belgian Study. (18th February 2014) - Catteau, Xavier; Simon, Philippe; Noël, Jean-Christophe
Abstract : Objectives . In Belgium, very few studies have focused on cervical high-risk human papillomaviruses (hrHPV) prevalence and the relationship between HPV and cervical cytological abnormalities. The aim of this study was to investigate hrHPV prevalence and its relationship with cytological screening and histological results in the French-speaking community in Belgium (Brussels and Wallonia). Methods . A total of 58, 265 liquid-based cytology tests were performed during this period. All cases of ASC-US, ASC-H, LSIL, and HSIL were tested by Hybrid Capture 2 for hrHPV screening. Results . The prevalence of cytological abnormalities was 3.1% for ASC-US, 0.3% for ASC-H, 1.5% for LSIL, and 0.3% for HSIL. The frequency of hrHPV infection was 47% in ASC-US, 90% in ASC-H, 86% in LSIL, and 98.4% in HSIL. CIN 2+ lesions were found in 12.2% of smears with an ASC-US result, in 54% of smears with an ASC-H result, in 12.5% of smears with a LSIL result, and in 89.3% of smears with a HSIL result. The ASC/SIL ratio was 1.9%. Conclusions . This study provides a good representation of cytological abnormalities and HPV status in patients living in Belgium's French-speaking community. The prevalence in our study was similar to that derived from meta-analyses of European studies. Our ASC/SIL ratio was 1.9%, being within the lower and upper limits proposed in the literature, which tends to prove the good quality diagnosis of cervical smears in our laboratory.